Analisis Kepuasan Pelanggan Terhadap Kualitas Layanan Produk Telkomsel Menggunakan Metode Servqual - Wahyudi Wahyudi; Sunarti Sunarti (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Competition amongs cellular operators are quite tight, trigger PT. Telkomsel to provide the best services and facilities to customers. Final goal of our research is to determine the level of customer satisfaction with quality of service Telkomsel product for Kartu As, services based on Short Message Service (SMS), General Packet Radio Service (GPRS), and Voice Call. This study used several analysis tools such as descriptive analysis, validity and reliability, Service Quality (Servqual) and the Customer Satisfaction Index (CSI). In this research there are several steps that do, the first phase of data collection from Telkomsel subscribers (Kartu As) to spread out the questionnaire, the second stage of data processing, to test the validity and reliability, and value calculation Servqual and CSI. The third stage is to draw conclusions from the results of data processing and analysis are performed. The results obtained show the high level of customer satisfaction on each of the services analyzed, namely for the SMS service of 0.75 (75%), GPRS of 0.69 (69%), and Voice Call by 0.71 (71%) .Keywords : Customer Satisfaction, Cellular Operators, SERVQUAL, Telkomsel